GEOCHEMICAL UNDERSTANDING OF VANADIUM IN MALMBERGET ORES (KIRUNA TYPE), NORTHERN SWEDEN - Kambai, Kabelo (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2021)
The Norrbotten region is an important Swedish mining district with occurrence of several economic deposits and sub-economic deposits of apatite iron ores (Kiruna Type) and epigenetic Cu-Au ores. The apatite iron ores include the large Malmberget deposit mined by LKAB company as one of their world class underground mines. The Malmberget ores are hosted by a Paleoproterozoic unit of metavolcanics and metasedimentary rocks intruded by multiple plutonic rocks varying in composition. The rocks at Malmberget are overprinted by intense widespread hydrothermal alteration, metamorphism and deformation. The Malmberget iron deposit is thought to originally be one continuous lens that segmented into more than 20 different orebodies during the regional metamorphism and deformation. The Malmberget deposit is characterized by different orebodies that shows different textures and chemical variations. The iron ores at Malmberget are mainly consisting of magnetite and hematite. Apatite iron ores of the Kiruna type have raised divergent opinions regarding whether this type of deposits are magmatic or hydrothermal in origin. However, trace element analysis have been used for studies that yield information about ore-forming fluids and mineralizing processes. This paper aims at understanding the vanadium behaviour and distribution in the Malmberget ores as well as studying textural and mineralogical control of vanadium in the iron ores. Learnings from this paper aids in understanding the controls and distribution of vanadium and increasing knowledge regarding genetic aspects of the Malmberget deposit. To achieve this, detailed core logging, optical microscopy, lithogeochemistry and scanning electron microprobe analyses were utilized to figure out why the vanadium content is high in some places and low in other parts of the deposit. Textural data of both magnetite and hematite ores show that the Malmberget ores can be characterized as massive ore and breccia type. The ores in the western part of the deposit are dominated by ...